Exploring Communicative Discourse of Millennials in Developing Social Entrepreneurship - Raudhatun Nafisah; Fathayatul Husna; Yusril Sahendra; Shinta Rizki Amanda (IJELR: International Journal of Education, Language, and Religion, 2023)
Social entrepreneurship is a crucial factor in the development of society, as it can greatly contribute to the well-being of individuals. The focus of this study is to examine how millennials use new media as a tool to promote and advance social entrepreneurship. Recognizing the relationship between new media and discourse, this study argues that entrepreneurship is geared towards creating social solidarity and encouraging individuals to change their mindset about how to increase profits, primarily through building social networks. This highlights the importance of conducting communication research to identify critical issues concerning the empowerment of millennials, especially in the context of new media. Our unit of analysis focused on a social entrepreneurial group called Mengayam Pesisir which is located in Bantul and Gunung Kidul areas, Yogyakarta.  We utilized a qualitative descriptive approach, employing virtual ethnographic methods that included in-depth interviews, online documentation, and literature studies. We found that Menganyam Pesisir engaged in communicative discourse as they worked to identify the problems and opportunities in the community. By identifying problems and shortcomings in society, social entrepreneurs can use communicative discourse to address these issues and bring about positive change.